The Specifics of Post-War Canadian Immigration Policy (1945–1957) - Burtseva, Mariia (Historia i Polityka, 2017)
Immigration plays a significant role in various areas of the society’s life and the international policy. Investigating the Canadian experience of immigration is one of the major elements for understanding different aspects of actual mass relocation. The principal objective of this study is to investigate the specifics of Canadian immigration policy following the Second World War. The research is based on analyzing legislation regulations that established Canadian immigration policy from 1945 to 1957. The findings indicated that there were multilateral causes for the after-war immigration changes. And that in reality, Canadian immigration policy in the post-war decade was quite ambiguous because of enacting liberal and discriminatory legislation at the same time.